PENGEMBANGAN BAKERY AICA PCA KEDUNGKANDANG MALANG - Fika Fitriasari; Titiek Ambarwati (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2020)
AICA PCA Kedungkandan Malang was established in 2017. AICA produces various bakeries that have a large market opportunity in the Malang area. In the future, this business can develop quite rapidly with various potentials owned by AICA Bakery, one of the characteristics of AICA products is that all ingredients used are halal and natural. The problems experienced by Bakery AICA are that marketing management is not yet optimal, there is no development of Human Resources management, and there is no ongoing assistance in business development, and the Patent Logo has not been registered. The results of this AICA bakery service development activity improve business management skills that are more professional starting from human resource management and marketing management. Bakery marketing is expanded by using social media and human resources or production department employees are added, so that AICA Bakery becomes a more productive business. Through the AICA PCA Kedungkandang Bakery mentoring program in the long run it can provide economic added value to the Muhammadiyah's charitable endeavors.